Physiological quality of chickpea seeds submitted to hydric and saline stress - Silva, Amanda Martins; Figueiredo, Josiane Cantuaria; Rodrigues Barbosa, Jorge Luiz; Souza da Silva, Elson Júnior; Tunes Madruga, Lilian Vanussa; Rodrigues, Daniele Brandstetter (Comunicata Scientiae, 2021)
The use of seeds of high physiological quality can be a strategy to reduce problems in the development of seedlings and allow the proper establishment of the stand under different environmental conditions, especially under stress conditions, such as water and saline. Thus, the objective was to evaluate the effect of water and salt stress on the physiological quality of seeds and on the growth of chickpea seedlings at different osmotic potentials, induced by polyethylene glycol 6000 (PEG) and sodium chloride (NaCl). The experiment was conducted in a completely randomized design, in a 2 x 5 factorial arrangement (two osmotic solutions, PEG and NaCl and five osmotic potentials, -0.2, -0.4, -0.6 and -0.8 MPa), with four replications of 200 seeds each. Initially, the water content of the seeds was determined. In the treatment effects, the physiological quality and initial seedling growth were evaluated (germination, first germination count, abnormal seedlings, germination speed index, average germination time, epicotyl and primary root length and dry mass of seedling). Osmotic potentials below -0.2 MPa reduces the germination and growth of chickpea seedlings, regardless of the stressor. Osmotic stress induced by NaCl produces more severe effects than PEG 6000 on the physiological quality of seeds